Chauncey M. Depew papers - Depew, Chauncey M. (Chauncey Mitchell), 1834-1928.
Correspondence and newspaper clippings relating to Depew's activities as official of the New York Central Railroad Company (1866-1928), senator from New York (1899-1911), and orator. Correspondents include Benjamin Harrison, Levi P. Morton, Whitelaw Reid, Theodore Roosevelt, and William Howard Taft.
Negative photocopies produced from originals in George Washington University, Washington, D.C.
George Washington University
U.S. senator, railroad official, author, and lecturer from New York.
Collection material in English.
Keywords: Harrison, Benjamin, -- 1833-1901 -- Correspondence; Morton, Levi P. -- 1824-1920 -- Correspondence; Reid, Whitelaw, -- 1837-1912 -- Correspondence; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Taft, William H. -- 1857-1930 -- Correspondence; New York Central Railroad Company; Railroads -- New York (State); United States -- Politics and government -- 1865-1933.; Authors; Lecturers; Railroad officials; Senators, U.S. Congress -- New York (State)